The effect of diaphragm fatigue on the multidimensional components of dyspnoea and diaphragm electromyography during exercise in healthy males. (8th June 2020) - Boyle, Kyle G.; Mitchell, Reid A.; Ramsook, Andrew H.; Schaeffer, Michele R.; Koehle, Michael S.; Sheel, A. William; Guenette, Jordan A.
Abstract : Key points: Diaphragm fatigue may increase the intensity (sensory dimension) and unpleasantness (affective dimension) of dyspnoea, which may partially explain why diaphragm fatigue negatively affects exercise performance. We hypothesized that diaphragm fatigue would negatively affect exercise performance via increases in both the intensity and unpleasantness of dyspnoea, and that the increase in dyspnoea would be mechanistically linked to an increase in diaphragmatic EMG (EMGdi ), a surrogate measure of neural respiratory drive. Fatiguing the diaphragm prior to exercise reduced cycling performance and increased both the intensity and unpleasantness of dyspnoea. The change in submaximal dyspnoea unpleasantness was significantly correlated with the change in cycling performance. Pre‐fatigue of the diaphragm did not increase EMGdi during exercise and is therefore unrelated to the increase in either the sensory or affective dimension of exertional dyspnoea. Abstract: The purpose of this study was to examine the effect of diaphragm fatigue on the multidimensional components of dyspnoea and diaphragm electromyography (EMGdi ) during cycling. Sixteen healthy males (age = 27 ± 5 yr, V ̇ O 2 max  = 45.8 ± 9.8 ml kg −1  min −1 ) completed two high‐intensity, time‐to‐exhaustion cycling tests in randomized order: (i) inspiratory pressure threshold loading (PTL) prior to exercise to induce diaphragm fatigue (pre‐DF) and (ii) no PTL (control). Diaphragm fatigue after PTL was confirmed via cervical magnetic stimulation of the phrenic nerves. Dyspnoea intensity and unpleasantness were measured throughout exercise with the 0–10 category‐ratio Borg scale and following exercise using the Multidimensional Dyspnoea Profile (MDP). EMGdi was continuously recorded via a multipair oesophageal electrode catheter. Time‐to‐exhaustion decreased with pre‐DF vs . control (9.0 ± 5.5 vs . 10.7 ± 7.5 min, P =  0.023). Pre‐DF increased dyspnoea intensity ratings by 0.6 ± 1.0 Borg 0–10 units at the highest equivalent submaximal exercise time (HESET) a participant could achieve in both conditions ( P =  0.020). Dyspnoea unpleasantness ratings increased with pre‐DF by 0.5 ± 1.0, 0.7 ± 1.2 and 0.9 ± 1.4 (all P  < 0.05) Borg 0–10 units during the 2nd, 3rd and 4th minutes of exercise, respectively. There was a significant correlation between the change in breathing unpleasantness ratings at HESET and the change in time‐to‐exhaustion ( r  = 0.66, P =  0.006). The immediate perception domain, a combination of peak unpleasantness and specific dyspnoea descriptor intensity ratings, was the only component of the MDP that was significantly increased with pre‐DF (4.3 ± 1.9 vs . 3.6 ± 1.8, P =  0.04). There were no significant differences in EMGdi . In conclusion, diaphragm fatigue has negative effects on multiple domains of dyspnoea, which may partially explain why exercise performance decreases with it. Key points: Diaphragm fatigue may increase the intensity (sensory dimension) and unpleasantness (affective dimension) of dyspnoea, which may partially explain why diaphragm fatigue negatively affects exercise performance. We hypothesized that diaphragm fatigue would negatively affect exercise performance via increases in both the intensity and unpleasantness of dyspnoea, and that the increase in dyspnoea would be mechanistically linked to an increase in diaphragmatic EMG (EMGdi ), a surrogate measure of neural respiratory drive. Fatiguing the diaphragm prior to exercise reduced cycling performance and increased both the intensity and unpleasantness of dyspnoea. The change in submaximal dyspnoea unpleasantness was significantly correlated with the change in cycling performance. Pre‐fatigue of the diaphragm did not increase EMGdi during exercise and is therefore unrelated to the increase in either the sensory or affective dimension of exertional dyspnoea.